The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge studies in contemporary philosophy, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"-- Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

The lived experiences of black undergraduate lesbian students at a rural South African university - Nela, K.; Vawdab, N.; Mbokodoc, L.; Govender, S. (Gender and Behaviour, 2017)
Malgré l'acceptation croissante des personnes lesbiennes, gays, bisexuelles, transgenres et intersexes (LGBTI), de nombreuses études indiquent encore que de nombreuses discriminations existent toujours. Les lesbiennes d'Afrique australe sont quotidiennement victimes de violences physiques et verbales et de viols correctifs. Le but de cette étude était d'explorer les expériences vécues par des étudiantes lesbiennes noires de premier cycle dans une université rurale en Afrique du Sud. Une approche de recherche qualitative utilisant un plan de recherche phénoménologique a été utilisée. L'échantillon était composé de quinze étudiantes lesbiennes noires de premier cycle âgées de 18 à 25 ans. Les données ont été collectées dans deux groupes de discussion et analysées à l'aide d'une analyse phénoménologique interprétative (IPA). L'homophobie, le harcèlement, y compris les agressions physiques, et la non-acceptation étaient des expériences quotidiennes chez les participantes lesbiennes. Cela incluait la discrimination de la part des pairs, du personnel universitaire et des organisations religieuses. Des expériences positives, comme la rencontre de nouveaux amis partageant la même orientation sexuelle et la découverte de l'université comme espace libre pour explorer leur sexualité, ont été trouvées.
Keywords: afrique; afrique du sud; approches et analyses; discipline; droits des femmes*; hétérosexisme; lesbophobie; personnes lesbiennes; psychologie; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; étudiantes de premier cycle

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"--Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Collection Santé et societé, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires